Pembangunan Sistem Informasi Manajemen Aset Pada Dinas Perikanan Kabupaten Tabanan - I Made Jeri Permana Adi; Denny Sagita Rusdianto; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Assets have an important role in operational activities at Dinas Perikanan Kabupaten Tabanan. It means that a good assets management is needed so it will not inhibit the operational activities. Assets reporting activities are conducted once every semester. In the reporting activities, data discrepancy is often occurred because there is no centralized place to store all the assets information. Therefore, a centralized information system to record all assets is needed to make them easier to manage. The information system is developed using waterfall model and implemented as a webservice. At the requirements analysis phase, 56 functional requirements and 1 non-functional requirements are obtained. The system design phase consists of 41 classes diagrams, with 9 classes are derived from the controller and 19 classes are derived from the model. The implementation phase uses Laravel 5.7 framework with the model-view-controller design pattern. Unit testing is carried out using 3 test samples with a base path testing method with 100% result. Validation testing is carried out with 100% result. Compatibility testing is also carried with 75% result that showed the system is running with critical issue on Firefox version 66 and Chrome version 74 and with major Issues on all platforms. While on IE version 11, Firefox version 66 and Safari version 12 the system runs with minor issues. Integration testing also conducted using integration incremental top-down with 100% result from 1 test sample.